The Influence Of CAR, FDR, BOPO, And TPF on the Profitability of Islamic Commercial Bank in Indonesia in the 2016-2020 Periode - Annisa Rakhmawati Respati Ningsih; Nana Diana (Fakultas Bisnis, 2022)
This study aims to determine the effect of CAR, FDR, BOPO, and TPF on the profitability (proxied by return on assets) of Islamic commercial banks in Indonesia in the 2016-2020 period . Data analysis in this study used a quantitative descriptive method. Data collection uses secondary data using a purposive sampling technique. The population is Islamic commercial banks in Indonesia and took 7 Islamic commercial banks to be used as samples. The sample has been tested using the classical assumption test and the analytical method used is multiple linear regression analysis . The results showed that the independent variables, namely CAR, FDR, BOPO, and TPF simultaneously had a significant effect on the dependent variable, namely ROA of 82.3%. While partially, the BOPO variable has no significant effect on ROA, while the CAR, FDR, and DPK variables have no effect on ROA.